Jak wyjaśnić dziecku, czym było Auschwitz? Annette Wieviorka: Czym było Auschwitz? Rozmowy z moją córką. Przeł. Paulina Tarasewicz. Gdańsk, Wydawnictwo w Podwórku, 2015, ss. 92 - Grzemska, Aleksandra (Narracje o Zagładzie [czasopismo zamknięte], 2016)
How to Explain to the Child What Auschwitz Was? Annette Wieviorka: Czym było Auschwitz? Rozmowy z moją córką. Przeł. Paulina Tarasewicz. Gdańsk, Wydawnictwo w Podwórku, 2015, ss. 92. In Auschwitz Explained to My Daughter – which is a conversation between Annette Wieviorka and her daughter Mathilde – a Jewish‑French historian describes to a French teenager, who is also a representative of the third generation descendent, what exactly Auschwitz was and how it has affected her life and her family’s lives. During this conversation Wieviorka has to face a difficult double role – of being a mother and a historian – and cope with complicated questions about the Holocaust experiences, which are in fact unspeakable, irrational, and out of any order.